Pengaruh Kompensasi Finansial dan Pelatihan terhadap Kinerja Karyawan Bagian Produksi pada PT. Navitasys Technology Indonesia Serang – Banten - Ratnasari, Intan; Lesmana, Ihwan Satria; Romli, Ombi (CV. Kalimasada Group, 2024)
Every company like PT. Navitasys Technology Indonesia definitely has goals to achieve. To achieve this goal, PT. Navitasys Technology Indonesia is very dependent on its human resources, in this case employees. The importance of the employee's role in achieving company goals must be balanced with the abilities possessed by the employee, meaning that the employee must be able to carry out every job assigned to him correctly and produce products with perfect results, both in quantity and quality. In other words, every employee must provide good performance for the company. The purpose of this research is to determine the partial and simultaneous influence of financial compensation and training on the performance of Production Department employees at PT. Navitasys Technology Indonesia. The method used in this research is a survey method, using a quantitative correlational approach, namely looking at cause-and-effect relationships. The sample used was part of the population in this study, namely 61 employees using the Slovin formula. This research can be concluded, either partially or simultaneously, that financial compensation and training have a significant effect on the performance of Production Department employees at PT. Navitasys Technology Indonesia, with an influential contribution of 30.8%, while the remaining 69.2% was influenced by other variables not discussed in this research.